Inhibitory effects of Indonesian temu kunci (Boesenbergia rotunda) rhizome extract on nitric oxide synthase production and on the kidneys of Wistar rats. (2022) - Rosdianto, Aziiz Mardanarian; Puspitasari, Irma Melyani; Lesmana, Ronny; Sumiwi, Sri Adi; Megantara, Sandra; Jiranusornkul, Supat
No abstract available